Induced Fitting and Polarization of a Bromine Molecule in an Electrophilic Inorganic Molecular Cavity and Its Bromination Reactivity. (8th July 2020) - Kikukawa, Yuji; Seto, Kensuke; Watanabe, Daiki; Kitajima, Hiromasa; Katayama, Misaki; Yamashita, Shohei; Inada, Yasuhiro; Hayashi, Yoshihito
Abstract: Dodecavanadate, [V12 O32 ] 4− (V12), possesses a 4.4 Å cavity entrance, and the cavity shows unique electrophilicity. Owing to the high polarizability, Br2 was inserted into V12, inducing the inversion of one of the VO5 square pyramids to form [V12 O32 (Br2 )] 4− (V12(Br2)). The inserted Br2 molecule was polarized and showed a peak at 185 cm −1 in the IR spectrum. The reaction of V12(Br2) and toluene yielded bromination of toluene at the ring, showing the electrophilicity of the inserted Br2 molecule. Compound V12(Br2) also reacted with propane, n‐butane, and n‐pentane to give brominated alkanes. Bromination with V12(Br2) showed high selectivity for 3‐bromopentane (64 %) among the monobromopentane products and preferred threo isomer among 2‐, 3‐dibromobutane and 2, 3‐dibromopenane. The unique inorganic cavity traps Br2 leading the polarization of the diatomic molecule. Owing to its new reaction field, the trapped Br2 shows selective functionalization of alkanes. Abstract : Bromine in a bottle : To accept the insertion of Br2, the bowl‐type structure of dodecavanadate was rearranged. Owing to the unique electrophilic feature of the bowl inside, Br2 was polarized such that it could be observed by IR spectroscopy. Polarized Br2 in a dodecavanadate bowl acted as an electrophilic reagent to achieve selective bromination of propane, n ‐butane, or n ‐pentane.